Efficacy and safety of Sahastara remedy for pain relief: A systematic review and meta-analysis of randomized controlled trials - Wiraphol Phimarn; Chatmanee Taengthonglang; Kritsanee Saramunee; Bunleu Sungthong (Shahrekord University of Medical Sciences, 2021)
The Sahastara (SHT) remedy is an herbal medicine that can be used as an alternative treatment for improving pain symptoms. The aim of this study was to evaluate the efficacy and safety of the SHT remedy for pain relief. PubMed, Scopus, ScienceDirect, TCI, and ThaiLis were systematically searched for relevant articles from inception to April 2021. We only included randomized clinical trials (RCTs) in which the efficacy and safety of the SHT remedy were compared with those of non-steroidal anti-inflammatory drugs (NSAIDs). Study selection, data extraction, and quality assessment were independently performed by two reviewers. The clinical therapeutic outcomes were the pain score, WOMAC score, Oswestry Disability Index score, 100 meters walk result, global assessment, and adverse events of the SHT remedy. The outcomes were assessed and pooled using a random-effects model. Heterogeneity was assessed using the I2 test. Four studies with 213 participants were included in the analysis. The efficacy of the SHT remedy was not different from that of NSAIDs in terms of the pain score (standardized mean difference [SMD] = -0.31; 95% CI = -1.26, 0.65; I2 = 91%), WOMAC score (SMD = 0.05; 95% CI = -0.30, 0.41; I2 = 0.0%), Oswestry Disability Index score (SMD = -0.41, 95% CI = -1.18, 0.35), 100 meters walk result (SMD = 0.31; 95% CI = -0.25, 0.87; I2 = 0.0%), and global assessment (relative risk = 0.85; 95% CI = 0.62, 1.16; I2 = 0.0%). Moreover, there were no statistically significant differences between the SHT remedy and NSAID treatment groups in terms of adverse events or liver function. This meta-analysis demonstrated that the SHT remedy is not different from NSAIDs in terms of clinical therapeutic efficacy and adverse events. However, larger and well-designed studies are needed to confirm this conclusion.